Functioning of patients after coronary artery bypass grafting - Jurkiewicz, Beata; Płaszewska-Żywko, Lucyna; Kołpa, Małgorzata (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2015)
Aim of the study was to assess biopsychosocial functioning of patients after CABG. Material and methods: The study was performed on 61 persons (18 women and 43 men) 48-81 years old (mean 65,3 ±7,8) who underwent the CABG procedure in the preceding 2-6 months and remained under the supervision of the Consultation Specialist Cardiology and Cardiac Surgery Clinic at Jan Paweł II Hospital in Cracow. The study was conducted from September 2012 to January 2013. The quality of life scale WHOQOL-BREF and a questionnaire constructed on the purpose of this survey were used in the study. Results: Eighty-two percent of patients noted very rare stenocardia symptoms after CABG, or none at all. The patients’ ability to perform everyday activities after the procedure improved (t = –8.8237, p < 0.001). Most patients observed no significant changes in terms of improving the possibilities of realization of their life plans (59.0%), improving their self-esteem (70.5%) or the meaning of life (60.7%). Also, most respondents showed no significant changes to social functioning. The patients were more satisfied with their quality of life (mean 3.5 ±0.9) than with their health condition (mean 3.4 ±0.9). Conclusions : Following the coronary artery bypass graft procedure, the comfort of living and the ability to perform everyday activities improved. Patients suffered from stenocardia symptoms significantly less often. In the psychological and social fields there were no significant changes.